Flower color-associated variation in phenolic content and antioxidant capacity in Portulaca grandiflora - LANI HARDIANY; ANNISA ZAHRA; AN’NISA ZAHRO NAFISAH; SILVIA SANTIKA; SYARIFAH IIS AISYAH; DINI DINARTY; WARAS NURCHOLIS (Society for Indonesian Biodiversity, 2026)
Abstract. Hardiany L, Zahra A, Nafisah AZ, Santika S, Aisyah SI, Dinarty D, Nurcholis W. 2026. Flower color-associated variation in phenolic content and antioxidant capacity in Portulaca grandiflora. Biodiversitas 27 (4): d270413. https://doi.org/10.13057/biodiv/d270413. Phenolic and flavonoid compounds are important plant secondary metabolites contributing to antioxidant defense through radical scavenging and redox-related mechanisms. Portulaca grandiflora is an ornamental species with diverse flower colors, yet information on the relationship between flower color, phytochemical composition, and antioxidant activity is limited. This study evaluated four defined flower color variants—Light Reddish Purple bicolor (LRP-bi), Strong Reddish Purple (SRP), Light Orange Yellow (LOY), and Brilliant Yellow (BY)—to determine Total Phenolic Content (TPC), Total Flavonoid Content (TFC), and antioxidant capacity using CUPRAC, FRAP, ABTS, and DPPH assays. Significant differences were observed among variants. SRP exhibited the highest TPC (3.98 mg GAE g⁻¹ FW) and the strongest reducing capacity, with CUPRAC values approximately 6.8-fold higher than LOY. In contrast, LOY and BY showed the highest TFC (1.15 and 1.09 mg QE g⁻¹ FW, respectively), while LRP-bi demonstrated the highest radical scavenging activity (ABTS and DPPH). Correlation analysis indicated strong positive associations between TPC and reducing power assays (r ≈ 0.87), whereas TFC showed negative relationships with antioxidant responses. These findings indicate that flower color is associated with variation in phenolic composition and antioxidant capacity, with red-purple variants exhibiting stronger reducing potential. Although based on a limited number of variants and in vitro assays, this study highlights flower color as a practical phenotypic indicator of phytochemical variation. This approach may support rapid screening, germplasm evaluation, and selection of ornamental plants with enhanced antioxidant-related traits.